2002
DOI: 10.1071/ar01115
|View full text |Cite
|
Sign up to set email alerts
|

Hardseededness in annual clovers: variation between populations from wet and dry environments

Abstract: Annual legumes rely on hardseededness, a form of seed dormancy, to spread the risk of mortality associated with germination and to encourage germination at the optimal time in a season. This paper examines seed softening strategies of a number of clover (Trifolium) species collected over a range of environments. Three hypotheses are tested. The first is that within species, long-term hardseededness increases with aridity due to the greater chance of failure to reproduce in dry environments. It is tested by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…Scimitar in this study, although the extent of seed softening was less in their study. The Lake Grace accession of T. tomentosum had much lower seed softening than in the study of Norman et al (2002), although both studies showed the greatest period of seed softening occurred in late autumn. A high residual hard-seed carryover into the seed bank appears important for annual legume persistence on saline land.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Scimitar in this study, although the extent of seed softening was less in their study. The Lake Grace accession of T. tomentosum had much lower seed softening than in the study of Norman et al (2002), although both studies showed the greatest period of seed softening occurred in late autumn. A high residual hard-seed carryover into the seed bank appears important for annual legume persistence on saline land.…”
Section: Discussionmentioning
confidence: 52%
“…A high residual hard-seed carryover into the seed bank appears important for annual legume persistence on saline land. On non-saline land hardseededness is widely recognised as a means of ensuring persistence of annual pasture legumes between seasons in the absence of seed production, such as can occur during severe cases of drought, flooding, insect attack, disease infection or overgrazing (Norman et al 1998(Norman et al , 2002 or after a cropping phase when grown in rotation with crops (Taylor et al 1991). Theoretical models (Cohen 1967;Venable and Brown 1988) indicate that as the level of environmental uncertainty increases, the requirement for long-term seed dormancy increases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variation in temperature and substrate moisture content among different burial periods and depths are considered key factors that influence PY-breaking in natural conditions (Norman et al 2002; Van Klinken et al 2006, 2008; Hu et al 2009). However, substrate moisture does not seem to play an important role in modulating PY- break of E. songoricum seeds under natural conditions.…”
Section: Discussionmentioning
confidence: 99%